Optimizing Trocar Depth for Effective Land Reclamation in Karbala: Combating Waterlogging and Salinity - Abdul Ameer Rasheed Saleh (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
This research explores the significance of field trocars in land reclamation within Karbala Governorate's Karta-10 area, caused by waterlogging and salinity. Implementing a detailed reclamation strategy, the study underscores the necessity of a 2 to 2.5 meters burial depth for trocars to prevent water and salt-related issues, aligning with industry standards. The investigation discourages reducing trocar depth to cut costs, as it can result in capillary action and salt build-up or require deeper drainage to manage seepage. Findings indicate that shallow trocars reduce water storage capacity, impacting irrigation and crop hydration, whereas deeper trocars offer better management of drainage flow and spacing efficiency. The study indorses a universal trocar depth of 2 to 2.5 meters, accommodating various crops, thus guiding optimal trocar design and placement for effective land reclamation.